From Micro Data to Causality: Forty Years of Empirical Labor Economics - Bas van der Klaauw (Institute for the Study of Labor (IZA), 2014)
This overview describes the development of methods for empirical research in the field of labor economics during the past four decades. This period is characterized by the use of micro data to answer policy relevant research question. Prominent in the literature is the search for exogenous variation in treatment assignment which can be exploited to estimate causal effects. With the increased availability of detailed administrative data empirical labor economics and more generally empirical microeconomics will become an even more prominent field in economics research.
Keywords: C21; C26; C93; J68; 330; treatment effects; endogeneity; selection; experiments; labor market behavior; microeconometrics